2014
DOI: 10.25215/0201.029
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Living of Elderly in Old Age Homes: An Exploratory Study

Abstract: Background: Now-a-days, almost all the old age homes (OAHs) in India are fully occupied with residents. Why Indian elderly have to reside in old age homes? It was explored during the Ph.D. study titled ‘A Study of Psychiatric Morbidity, Quality of Life and   Expectations of Inmates of Old Age Homes in Northern India’. The object of this study was to explore the factors compelling elderly to reside in old age homes.  Methods: This study was carried out on 174 elderly residing in 14 different OAHs of Uttar Prade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The government old age homes often seen as places of loneliness and staffs are unqualified without proper training. 7 During this pandemic, fear of COVID-19 infection, inadequate care, lack of adequate food resources and self-quarantine conditions in government old age homes have major influence on Nutritional and Emotional wellbeing of elders. The present cross sectional questionnaire survey was aimed to evaluate and correlate the nutritional status, emotional wellbeing along with dentition & prosthetic rehabilitation status among geriatric individuals during Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The government old age homes often seen as places of loneliness and staffs are unqualified without proper training. 7 During this pandemic, fear of COVID-19 infection, inadequate care, lack of adequate food resources and self-quarantine conditions in government old age homes have major influence on Nutritional and Emotional wellbeing of elders. The present cross sectional questionnaire survey was aimed to evaluate and correlate the nutritional status, emotional wellbeing along with dentition & prosthetic rehabilitation status among geriatric individuals during Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…At present, elderly care and needs are major challenges worldwide. [7][8][9] Nutrition and Emotional wellbeing are considered as elder's resilience against COVID-19 infection. From the literature reports, it was found that nutritional deficiency was more severe among elders, 35-65% of elderly hospitalized patients, and 25-60% of institutionalized older adults were found to be suffering from malnourishment.…”
Section: Introductionmentioning
confidence: 99%
“…They are commonly perceived as a burden to family and society, making them all the more vulnerable to physical and emotional abuse, abandonment and financial crisis. This compels them to opt for other places to live a free and respectful life, and old age homes are often their only support to do so (4,9). Depressive symptoms have been found to be more common in institutionalized old people.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Lastly, 11.67% of care home residents acknowledged that the need for specialized care and attention for seniors, which may not be readily available at home, was their primary motivation. This data provides valuable insights into the multifaceted reasons that drive individuals to seek care home admission [13,14,15].…”
Section: Reasons Of Inmates For Joining the Care Homementioning
confidence: 99%